2004
DOI: 10.1097/01.blo.0000150129.65400.78
|View full text |Cite
|
Sign up to set email alerts
|

Major Femoral Bone Loss in Revision Total Hip Arthroplasty Treated with Tapered, Porous-Coated Stems

Abstract: Clinical results of revision total hip arthroplasty using fully porous-coated tapered titanium stems to treat severe proximal femoral bone loss were evaluated in a retrospective review of 39 patients (45 hips). The bone was reinforced with cables in 39 hips, and in 14 hips strut allografts were added. Fixation was successful in 44 hips, and one hip required revision to treat undetected fracture and migration of the stem. All the others had radiographic evidence of bone attachment. Neither bone atrophy nor reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The large, patulous joint and poorly constrained ROM predispose the hip to dislocation [5,13]. The series in this article is too small to establish the effect of this procedure on dislocation rate, but addition of a posterior muscle flap in cases of severe capsular deficiency probably stabilizes the hip and protects against instability.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The large, patulous joint and poorly constrained ROM predispose the hip to dislocation [5,13]. The series in this article is too small to establish the effect of this procedure on dislocation rate, but addition of a posterior muscle flap in cases of severe capsular deficiency probably stabilizes the hip and protects against instability.…”
Section: Discussionmentioning
confidence: 92%
“…Loss of the ligament and muscle control of the hip is likely responsible for the high rate of dislocation after revision THA [5,13]. The large, patulous joint and poorly constrained ROM predispose the hip to dislocation [5,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many surgeons presume proximally coated stems, or cemented stems, have a lower incidence of thigh pain than fully coated stems, this remains controversial [1,2,17,25,28,30,38]. Most authors recognize the reported incidence of thigh pain will be influenced by the way a patient is asked about its presence, a point best controlled with a prospective randomized blinded clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Femoral bone loss or resorption, so-called stress shielding, around well-fixed femoral components is thought to occur around most, if not all, stem designs [12,32,34,38]. This phenomenon is reportedly exacerbated with fully coated stems [12,15,18].…”
Section: Introductionmentioning
confidence: 99%